Investigation Of The Factors That Affect Employee Well-Being In The Indian IT Sector - Simran, Shreya; Das, Debi Prasad (Migration Letters, 2024)
An important portion of India’s population has access to employment opportunities thanks to the IT sector, which has long been a pillar of the country’s economic growth. Employee well-being (EWB) is widely recognized as being important in all industries and employee categories and is receiving a lot of attention in recent research. In order to create a comprehensive EWB measurement scale specifically for IT employees, this paper offers an innovative method called exploratory and confirmatory factor analysis (EFA) and confirmatory factor analysis (CFA). A questionnaire with 45 EWB scale items was painstakingly created with the help of existing literature and expert consultations in order to achieve this goal. The responses of 121 participants were used to evaluate the applicability of each scale item. The 33 EWB scale items that were most relevant for further factor analysis were determined using a Content Validity Ratio (CVR) analysis. Data gathered from 384 respondents working in the Indian IT sector were used to carry out EFA. The 33 EWB scale items were divided into four groups as a result of this process: psychological well-being, social well-being, workplace well-being, and subjective well-being. These 33 EWB scale items within the four identified groups were then validated using various indices using CFA in the SPSS AMOS software. The paper also explores how this research’s practical applications and implications relate to the health of IT workers in India.